Transformation of Student Investment Behavior: An Analysis of Determining Factors with Financial Literacy as an Intervening Variable - Rudi Ananda; Hadli Hadli; Nabila Grahana Putri; Naura Ilgalia Putri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the transformation of student investment behavior by identifying the determining factors influenced by financial literacy as an intervening variable. The variables observed include risk level, return level, access to information, information motivation, literacy, and investment decisions. The population of this study was active students of the Accounting Study Program at a private university in Palembang with a sample size of 285 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that: 1) Access to information has a positive effect on investment decisions, 2) Access to information affects financial literacy, 3) Financial literacy plays a role in influencing investment decisions, 4) Investment motivation affects investment decisions, 5) Investment motivation also influences financial literacy, 6) Return rate significantly influences investment decisions, 7) Return rate influences financial literacy, 8) Risk level influences investment decisions, and 9) Risk level also influences financial literacy. These findings indicate the importance of financial literacy in shaping students' investment decisions, especially in relation to perceptions of risk and return